2019
DOI: 10.3390/coatings9110734
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Mo2N Films at Elevated Temperature

Abstract: Mo2N films were synthesized using the reactive magnetron sputtering system in a mixture of argon and nitrogen, and the tribological properties were investigated at different testing temperatures against an Al2O3 counterpart. The relative intensity ratio (RIR) method was used to calculate the weight fraction of the tribo-film (MoO3) on the wear tracks of the films. The results showed that the average friction coefficient first increased from 0.30 at 25 °C to 0.53 at 200 °C, and then decreased to 0.29 at 550 °C,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…However, this value is due to the gradual elimination of oxides and the surface's homogeneity. These results are in good agreement with those of other recent studies [43][44][45].…”
Section: Variation Of Friction Coefficient As a Function Of Mon Film ...supporting
confidence: 94%
See 1 more Smart Citation
“…However, this value is due to the gradual elimination of oxides and the surface's homogeneity. These results are in good agreement with those of other recent studies [43][44][45].…”
Section: Variation Of Friction Coefficient As a Function Of Mon Film ...supporting
confidence: 94%
“…We notice that the friction coefficient of the MoN film tested against a Si3N4 ball is between 0.55 and 0.93. The COF is close to that obtained for the sputtered MoN films [43].…”
Section: Variation Of Friction Coefficient As a Function Of Mon Film ...supporting
confidence: 84%
“…It is worth emphasizing that V and Mo substitutions in TMN have often been shown to improve both the coatings' resistance to corrosion [64][65][66] as well its tribological properties [67][68][69]. The latter effect it due to the formation of lubricant V2O5 and MoO3 oxide phases during machining processes [70][71][72][73]. Very recent tribology testing experiments conducted on V-Mo-N coatings have, in fact, shown that vanadium molybdenum nitride is a promising high-temperature selflubricant material [74,75].…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, it is reported in Ref. [22-24] that MoO 3 is a Magneli phase with solid-lubricating properties: MoO 3 has a layered structure, it relies on the van der Waals force between layers and has a weak binding force, so MoO 3 is easily sheared layer by layer, and has the lubricity to reduce fraction, so that more MoO 3 oxidation phase contributes to the lower μ .
Figure 8 XRD pattern of the wear track on the Ti–Al–Mo–N films with 8.2 and 49.4 at.-% Mo.
…”
Section: Resultsmentioning
confidence: 99%
“…Magnéli phases are usually considered as solid-lubricant oxides, because they consist of layers that are combined by van der Waals force, which are easy to deform under shear. Appropriate amounts, such as V, Mo, and B, are considered as potential additions into TMN-based films [21][22][23], which enable to improve the tribological properties of the films. Mo can form Magnéli phase MoO 3 during the wear test, which can effectively reduce the friction coefficient of films [24].…”
Section: Introductionmentioning
confidence: 99%